Effect of molases addition on survival and growth of tiger shrimp Penaeus monodon Fab. larva treated with SKT-b Vibrio probiotic bacteria - Widanarni, ,; Saputra, Wira H; Wahjuningrum, Dinamella (Indonesian Society of Scientific Aquaculture (ISSA), 2011)
ABSTRACTProbiotic bacteria SKT-b Vibrio that belong to heterotrophic bacteria have been tested can suppress the growth of pathogenic Vibrio harveyi in tiger shrimp larvae. One of the most important energy sources of heterotrophic bacteria is organic carbon such as sucrose and glucose found in molasses. The objective of this experiment was to study the effect of molasses addition on the survival and growth rate of tiger shrimp Penaeus monodon larvae treated with SKT-b Vibrio probiotic bacteria. This experiment was done both in vitro and in vivo. In vitro tests performed by growing bacteria in media containing molasses, fish meal and premix. Whereas in vivo tests performed with the addition of molasses to shrimp larva culture media inoculated with SKT-b Vibrio bacteria which included five treatments: the control treatment without bacteria and molasses addition (K), the addition of bacteria without molasses (B), the addition of molasses 1 ppm and bacteria (MB1), the addition of molasses 3 ppm and bacteria (MB3), and the addition of molasses 5 ppm and bacteria (MB5). The result of in vitro tests showed the SKT-b Vibrio bacteria can grow on molasses media with a population reached 0,41 × 108 CFU/ml. In vivo test results showed that treatment MB3 gave the highest survival (93.3%) and growth weight (35.94%), but were not significantly different from control result in the survival and growth weight that respectively were 83.3% and 30.38%.Keywords: probiotic bacteria, SKT-b Vibrio, molasses, tiger shrimp larvae ABSTRAKBakteri probiotik Vibrio SKT-b yang tergolong bakteri heterotrof telah diuji dapat menekan pertumbuhan Vibrio harveyi yang bersifat patogen pada larva udang windu. Salah satu sumber energi yang paling penting bagi bakteri heterotrof adalah karbon organik seperti sukrosa dan glukosa yang terdapat pada molase. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penambahan molase terhadap kelangsungan hidup dan pertumbuhan larva udang windu Penaeus monodon Fab. yang diberi bakteri probiotik Vibrio SKT-b. Penelitian dilakukan secara in vitro dan in vivo. In vitro yaitu menumbuhkan bakteri pada media yang mengandung molase, tepung ikan dan premix. In vivo yaitu penambahan molase pada media pemeliharaan udang yang diberi bakteri probiotik Vibrio SKT-b, yang meliputi lima perlakuan yakni: perlakuan kontrol tanpa penambahan bakteri maupun molase (K), penambahan bakteri tanpa molase (B), penambahan molase 1 ppm dan bakteri (MB1), penambahan molase 3 ppm dan bakteri (MB3), penambahan molase 5 ppm dan bakteri (MB5). Hasil uji in vitro menunjukkan bakteri Vibrio SKT-b dapat tumbuh pada media molase dengan populasi mencapai 0,41×108 CFU/mL. Hasil uji in vivo menunjukkan perlakuan MB3 menghasilkan kelangsungan hidup (93,3%) dan pertumbuhan bobot (35,94%) tertinggi, namun tidak berbeda nyata dengan kontrol yang menghasilkan kelangsungan hidup dan pertumbuhan bobot berturut-turut 83,3% dan 30,38%.Kata kunci: bakteri probiotik, Vibrio SKT-b, molase, larva udang windu